Towards Shrimp Resources Investment in Iraq water - Ali, Malik H. (Iraqi Journal of Aquaculture, 2021)
The article highlighted the global importance and production of shrimp resources, whether it’s coming from the fisheries or from the aquaculture sector as well as it’s economy attribute in the international trade. Furthermore, it’s recognizing the status of the shrimp fishery in the marine and inland waters of Iraq, and the main negative factors impacted and reducing the shrimp stocks. Apparently no practical attempt has already been undertaken to culture the shrimp in the area, despite the availability of diverse water bodies. In conclusion, there is a great opportunity to developing the shrimp resources sector in Iraq by: (1) introduction and developing shrimp culture, (2) improving better management system for the shrimp fisheries.